Synthesis and Characterization of New Bidentate Schiff Base Ligand Type (NO) Donor Atoms Derived from Isatin and 3-Amino Benzoic Acid and Its Complexes with Co(II), Cu(II), Cd(II) and Hg(II) Ions - Alkam, Heam Hadi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New bidentate Schiff base ligand (L) namely [(Z)-3-(2-oxoindolin-3ylildeneamino)benzoic acid] type (NO) was prepared via condensation of isatin and 3-amino benzoic acid in ethanol as a solvent in existence of drops of (glac. CH3COOH). The new ligand (L) was characterized base on elemental microanalysis, FT-IR, UV-Vis, 1H-NMR spectra along with melting point. Ligand complexes in general formula [M(L)2Cl2]. H2O, where: MII = Co, Cu, Cd, and Hg; L= C15H10 N2O3 were synthesized and identified by FT-IR, UV-Vis, 1H-NMR (for Cd complex only) spectra, atomic absorption, chloride content along with molar conductivity and magnetic susceptibility. It was found that the ligand behaves as bidentate on complexation via (N) atom of imine group and (O) atom of carbonyl group of five member ring. The electronic spectral data and Âµeff values (Co, Cu) of the complexes exhibited octahedral geometry around CoII, CuII, CdII, HgII metal ions. The results of antibacterial activity showed that only Hg(II) complex has high activity (35 mm) for staphylococcus aureas.